2020
DOI: 10.1177/0967391120943461
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibre pretreatments on characteristics of green fabric materials

Abstract: The use of natural fibres as composite reinforcements is inevitable in view of developing a sustainable environment. When a natural fibre is extracted from a plant or ground or animal, they are prone to contain impurities and other unwanted substances. By removing these unwanted substances and by enhancing the strengths of the fibres, the reinforcements become predominant to carry the loads in a composite material and thus help the composite to acquire major mechanical properties. Hence, pretreatment methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…The counter face may be adjusted more easily and the transfer film forms more quickly when a high load is applied. Low wear rate is achieved at a larger load because the transfer film created in this way shields the soft polymer surface from the hard metal surface [42][43][44][45] Sliding distance has very little of an impact on the SWR. It reduces until 40% of fibre content and then elevates for further increase.…”
Section: Resultsmentioning
confidence: 99%
“…The counter face may be adjusted more easily and the transfer film forms more quickly when a high load is applied. Low wear rate is achieved at a larger load because the transfer film created in this way shields the soft polymer surface from the hard metal surface [42][43][44][45] Sliding distance has very little of an impact on the SWR. It reduces until 40% of fibre content and then elevates for further increase.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by R. Vinayagamoorthy [21], special attention was paid to the damage of textile fibres during hydrothermal treatment. Studies have shown that humidity and elevated temperature, accompanied by this process, can weaken intermolecular bonds in fibres, which leads to their destruction and deformation.…”
Section: Discussionmentioning
confidence: 99%
“…mechanical, physical, chemical and biological to raw materials used to manufacture green composites may improve the mechanical and physical characteristics of GC. 68 In Figure 4 are mentioned the main effects on the raw materials after the pretreatment and their particular characteristics; these effects might impact some physical and chemical properties of composites and are explained in detail in further sections.…”
Section: Physical and Chemical Characteristics Of Renewable Recyclable And Biodegradable Compositesmentioning
confidence: 99%